Petumbuhan dan Perkembangan Ekonomi Makro Syariah di Indonesia - Aye Sudarto (Institut Agama Islam Agus Salim Metro Lampung, 2020)
Abstract Macroeconomics that play an important role can often have a serious impact on a country's growth. We can mention one by one what is part of the macro economy that affects the national economy are low economic growth, poverty and unemployment, inflation, low rupiah exchange rate, energy crisis, state budget deficit, and imbalance of trade balance and payments become adult national economic problems this. In view of the growth, development, opportunities and challenges of sharia macroeconomics in Indonesia, it is important that we first understand the economic system adopted by Indonesia today. As we know that what determines the shape of an economic system except the basis of a state philosophy that is upheld, the criteria are institutions, especially economic institutions that become the manifestation or realization of the philosophy. Sharia Macroeconomics in Indonesia is not yet signi ï¬ cant in influencing macroeconomic conditions in Indonesia, due to its small assets compared to conventional economies. Indonesia has the potential to be able to position itself as the center of World Sharia finance. We have strong capital to make this happen, because besides Indonesia is the largest Muslim country in the world, Indonesia is also a member of the G-20 and a country with the fifth largest population in the world that has a rapidly growing middle income. Sharia economy and finance can make a very significant contribution in lifting the quality of the Indonesian economy. Keyword : Macroeconomics, Sharia Macroeconomics, Sharia Finance